2007
DOI: 10.1111/j.1600-0714.2007.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral cancer and pre‐cancer and associated risk factors among tea estate workers in the central Sri Lanka

Abstract: The prevalence of oral pre-cancer in tea estate labourers was higher than estimates reported in previous studies. In the absence of state-sponsored preventive activities, it is necessary to improve the capacity of individual health practitioners and small medical centres to participate in oral health promotion and oral cancer/pre-cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 26 publications
(27 reference statements)
7
46
1
2
Order By: Relevance
“…A recent work conducted in Delhi, India by Goyal et al (2014) revealed that Majority cases were doing small business and either unemployed or labourer, more than half patients were from income less than Rs 10,000 (approximately US$ 200) per month and 10 % were from weaker section of society. In line to previous studies (Bhurgri, 2005;Ariyawardana et al, 2007;Warnakulasuriya, 2009;Hosseinpoor et al, 2012) from Asian countries have also reported that low socioeconomic status is a risk factor for oral cancer.…”
Section: Discussionsupporting
confidence: 89%
“…A recent work conducted in Delhi, India by Goyal et al (2014) revealed that Majority cases were doing small business and either unemployed or labourer, more than half patients were from income less than Rs 10,000 (approximately US$ 200) per month and 10 % were from weaker section of society. In line to previous studies (Bhurgri, 2005;Ariyawardana et al, 2007;Warnakulasuriya, 2009;Hosseinpoor et al, 2012) from Asian countries have also reported that low socioeconomic status is a risk factor for oral cancer.…”
Section: Discussionsupporting
confidence: 89%
“…People doing manual occupations such as agriculture, labouring, and working in industries, are at increased risk for developing OC (Dhar et al, 2000;Balaram et al, 2002;Muwonge et al, 2008). In Sri Lanka, for example, tea estate workers are a high risk population (Ariyawardana et al, 2007). Odds ratio (OR) of 2.5-2.8 has been calculated for development of OC among farmers in India (Subapriya et al, 2007;Madani et al, 2010a;Pawar et al, 2012).…”
Section: Socioeconomic Conditions (Sec)mentioning
confidence: 99%
“…Betel quid, smoking and alcohol have a synergistic effect on the development of leokoplakia another pre cancerous condition. The risk for precancerous lesions were highest among betel chewers (OR 3.01) followed by smoking (OR 2.16) and alcohol (OR 1.41) among tea estate labourers 5 . Betel quid chewing is also associated with cancer of the pharynx and oesophagus 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In 1982, a study among Sri Lankan villagers found 54% of males and 42% of females to use betel regularly 4 . A study among tea estate labourers found that 92% with oral mucosal lesions reported betel quid chewing 5 . Population based studies in India, Nepal and Pakistan over the past 25 years have found 20-40% of those aged 15 years and over were betel quid or areca nut chewers 1 .…”
Section: Introductionmentioning
confidence: 99%